IMPACT OF SOCIO-CULTURAL FACTORS ON DEMAND FOR INSURANCE POLICY AND PRODUCT IN NIGERIA - Rukayat Bukola ADEJARE; Ismaila Daudu ALIU (Malete Journal of Accounting and Finance)
The insurance sub-sector of financial services industry aims at smoothening financial distortions in the economy. However, the sector is weak due to inappropriate response to economic challenges. The potential of the insurance industry in emerging countries like Nigeria is being hampered by socio-cultural attributes of the customers which include many dimensions such as language, education, ethnic background and religion. These factors make customers to be skeptical in deciding on insurance policies which consequently lead to poor penetration and poor performance of the insurance sector. As a result, the present study examines the impact of socio-cultural factors on the taking up of insurance policy in Nigeria. The study adopts survey research design and the sample size is 384 respondents and the data obtained was analyzed using descriptive and inferential statistics. The result of analysis reveals that Christian religious belief, language, trust, and level of awareness of customers statistically and significantly influence the extent of procurement of insurance policy by customers in Nigeria. However, the Islamic religious belief and ethnicity of the customers do not have statistically significant relationship with demand for insurance policy. The study concludes that Christianity, trust and level of awareness of customers influence their demand for insurance policy in Nigeria. Consequently, insurance companies should strengthen the level of trust between their agents and the customers and should widen their level of publicity in order to improve demand for insurance policy in Nigeria.